Social networs and identity: Teen challenge? - Lardies, Felicita (2022)
The following is an article of bibliographic review and critical analysis of the influence of social networks on the identity construction in contemporary adolescence. During adolescence, the construction of a personally significant and socially accepted identity is the core task of this life stage. This process has to be understood and addressed considering that social networks have an important place for contemporary adolescences.